2006
DOI: 10.1074/jbc.m511019200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Hypoxia-inducible Form of 6-Phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3)

Abstract: The hypoxia-inducible form of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3) plays a crucial role in the progression of cancerous cells by enabling their glycolytic pathways even under severe hypoxic conditions. To understand its structural architecture and to provide a molecular scaffold for the design of new cancer therapeutics, the crystal structure of the human form was determined. The structure at 2.1 Å resolution shows that the overall folding and functional dimerization are very similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 45 publications
(43 reference statements)
1
57
0
Order By: Relevance
“…In the recently solved crystal structure of PFKFB3, the carboxyl terminus appears flexible and disordered (28,42), suggesting a discrete function. We have found that the dominantly expressed splice variant of PFKFB3 localizes to the nucleus and that the carboxyl terminus is required for this localization.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently solved crystal structure of PFKFB3, the carboxyl terminus appears flexible and disordered (28,42), suggesting a discrete function. We have found that the dominantly expressed splice variant of PFKFB3 localizes to the nucleus and that the carboxyl terminus is required for this localization.…”
Section: Discussionmentioning
confidence: 99%
“…Residues 4-15 of the kinase domain form a β-hairpin structure and the rest is used as an arm connecting the hairpin to the bisphosphatase domain. Additionally, the contacting area of the bisphosphatase domain is functionally very sensitive due to the residues critical for binding of both product and substrate are located very close (Kim et al, 2006). The low bisphosphatase activity of PFKFB3, which is lower than that of other isoforms by an order of magnitude, is due to the presence of a serine at residue 302 instead of an arginine as conserved in the other isoforms.…”
Section: Proteinmentioning
confidence: 92%
“…The conformations of the substrate loops in the kinase domain are different from those of other isoforms (Hasemann et al, 1996;Lee et al, 2003), giving a structural explanation for the higher kinase activity. Moreover, the N-terminus binds to the bisphosphatase domain to produce a conformational change in the active pocket to enhance inhibitory binding of product (Kim et al, 2006). Residues 4-15 of the kinase domain form a β-hairpin structure and the rest is used as an arm connecting the hairpin to the bisphosphatase domain.…”
Section: Proteinmentioning
confidence: 99%
See 2 more Smart Citations